Sunitinib suppress neuroblastoma growth through degradation of MYCN and inhibition of angiogenesis. - Raul Calero; Esther Morchon; John Inge Johnsen; Rosario Serrano (PLoS ONE)
Neuroblastoma, a tumor of the peripheral sympathetic nervous system, is the most common and deadly extracranial tumor of childhood. The majority of high-risk neuroblastoma exhibit amplification of the MYCN proto-oncogene and increased neoangiogenesis. Both MYCN protein stabilization and angiogenesis are regulated by signaling through receptor tyrosine kinases (RTKs). Therefore, inhibitors of RTKs have a potential as a treatment option for high-risk neuroblastoma. We used receptor tyrosine kinase antibody arrays to profile the activity of membrane-bound RTKs in neuroblastoma and found the multi-RTK inhibitor sunitinib to tailor the activation of RTKs in neuroblastoma cells. Sunitinib inhibited several RTKs and demonstrated potent antitumor activity on neuroblastoma cells, through induction of apoptosis and cell cycle arrest. Treatment with sunitinib decreased MYCN protein levels by inhibition of PI3K/AKT signaling and GSK3β. This effect correlates with a decrease in VEGF secretion in neuroblastoma cells with MYCN amplification. Sunitinib significantly inhibited the growth of established, subcutaneous MYCN-amplified neuroblastoma xenografts in nude mice and demonstrated an anti-angiogenic effect in vivo with a reduction of tumor vasculature and a decrease of MYCN expression. These results suggest that sunitinib should be tested as a treatment option for high risk neuroblastoma patients.